Sulle tracce del principio di giustizia. Diritto alla salute e consenso informato all’atto medico nel diritto europeo (Stato, Chiese e pluralismo confessionale, 2025)
On the trail of the principles of justice. Right to health and informed consent to the medical act in European lawThe right to health and the right to informed consent are related to the principle of justice. It is a principle that requires respect for the person, human dignity and the fundamental rights of every human being. It constitutes the backbone of the European Union, one of the fundamental principles that has led the construction of European law and aims to ensure that European laws and policies are fair and impartial. Its traces emerge in both the European Treaties and the EU Charter of Fundamental Rights. The paper aims to analyze the impact of the principle of justice on the right to health and the right to informed consent in European law, including with reference to the metaphysical and transcendental dimensions of the person, in order to highlight inadequacies, shortcomings, and strategies for intervention.SOMMARIO: 1. Brevi considerazioni introduttive - 2. Il bene salute nel diritto europeo - 3. Il consenso informato nella Convenzione sui Diritti dell’Uomo e la biomedicina - 4. La Carta europea dei diritti del malato tra tutela del diritto alla salute e salvaguardia del consenso informato - 5. Il diritto alla salute: limiti normativi e strategie d’intervento - 6. Consenso informato e 'adeguatezza' delle informazioni mediche: prospettive di perfezionamento e questioni emerse durante l’emergenza sanitaria da Sars-Cov-2 - 7. In somma.